2015
DOI: 10.1371/journal.pone.0137810
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prevents Memory Impairment Induced by Arsenic Exposure in Mice: Implication of Hippocampal BDNF and CREB

Abstract: High concentrations of arsenic, which can be occasionally found in drinking water, have been recognized as a global health problem. Exposure to arsenic can disrupt spatial memory; however, the underlying mechanism remains unclear. In the present study, we tested whether exercise could interfere with the effect of arsenic exposure on the long-term memory (LTM) of object recognition in mice. Arsenic (0, 1, 3, and 10 mg/ kg, i.g.) was administered daily for 12 weeks. We found that arsenic at dosages of 1, 3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…Several studies have shown a strong correlation between increased levels of circulating BDNF and exercises, yet no studies have shown an increase in BDNF levels with WBV. One study has shown that exercise in mice is effective at preventing a decrease in BDNF levels in the CA1 and dentate gyrus that would otherwise be caused by exposure to Arsenic [60]. It is proposed that training to volatile fatigue is the optimal way to increase circulating BDNF levels in elderly participants [61].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a strong correlation between increased levels of circulating BDNF and exercises, yet no studies have shown an increase in BDNF levels with WBV. One study has shown that exercise in mice is effective at preventing a decrease in BDNF levels in the CA1 and dentate gyrus that would otherwise be caused by exposure to Arsenic [60]. It is proposed that training to volatile fatigue is the optimal way to increase circulating BDNF levels in elderly participants [61].…”
Section: Discussionmentioning
confidence: 99%
“…cAMP/protein kinase A (PKA), ERK1/2 Mitogen‐Activated Protein Kinase, nitric oxide pathway, histone acetyltransferase (HAT) and histone deacetylases (HDACs) are examples of these pathways which contribute in P‐CREB formation and thereby, memory processing . According to the previous investigations, increased phosphorylation of CREB and expression of P‐CREB in the hippocampus and the basolateral amygdala facilitate memory formation and consolidation. Moreover, Kenney et al, showed that nicotine‐induced improvement of memory is dependent on the elevation of P‐CREB expression in the hippocampus, while cannabinoids impair memory formation due to reduction of P‐CREB expression levels .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a strong correlation between increased levels of circulating BDNF and exercises, yet no studies have shown an increase in BDNF levels with WBV. One study has shown that exercise in mice is effective at preventing a decrease in BDNF levels in the CA1 and dentate gyrus that would otherwise be caused by exposure to Arsenic [ 51 ]. It is proposed that training to volatile fatigue is the optimal way to increase circulating BDNF levels in elderly participants [ 52 ].…”
Section: Discussionmentioning
confidence: 99%